Traditionsgeschichtliche Erwägungen zur Namenlosigkeit von Jiftachs Tochter (Ri 11,29-40) - Bauks, Michaela 1962- (2007)
The namelessness of Jephthahs daughter is an often discussed theme of feminist exegesis. The author tries to give traditional-historical explanations for this phenomen and compares the pattern with traditions from Ancient Greece (Iphigeneia and Korès-tradition). Thus, the pattern does not describe the reduction of the daughter to a submissive victim, but gives a rare indication of an initiation rite for girls in the Old Testament.